Consumption trends of alpha-lipoic acid: drugs vs. dietary supplements in the Republic of Serbia - Vuković, Milana; Jovičić Bata, Jelena; Todorović, Nemanja; Čanji Panić, Jelena; Vesković, Dunja; Lalić-Popović, Mladena (Archives of Pharmacy, 2024)
On the Serbian market, alpha-lipoic acid (ALA) is available in 7 drug formulations and over 50 dietary supplements (DS). This study aimed to analyze and compare the consumption of ALA drugs and DS. The data on drug consumption were obtained from the annual reports of the Medicines and Medical Devices Agency of Serbia, while the data for DS were sourced from IMS Health's monthly audit reports. The consumption of ALA drugs significantly increased during 2010-2016 (R² = 0.753, F(1, 5) = 15.219, p = 0.011), with a notable drop observed in 2017. The consumption of ALA DS surged by 156.67% from 2018 to 2020, reaching 0.77 DDD/1000 inhabitants/day, with a notable increase observed at the end of 2020. From January to October 2021, the consumption doubled compared to the same period in 2020, reaching 1 DDD/1000 inhabitants/day. The increase in ALA drug consumption during 2010-2016 paralleled the registration and clinical adoption of ALA drugs. A significant drop in 2017 might have resulted from registering new ALA DS. However, during 2018-2020, ALA drugs were more commonly consumed compared to ALA DS. The increased consumption of ALA DS at the end of 2020 was associated with the COVID-19 epidemic. While both drugs and DS offer 600 mg ALA doses, only drug regulations ensure quality and efficacy, highlighting the need for stricter regulations on DS to enhance consumer safety and information.
Keywords: alpha-lipoic acid; dietary supplements; consumption trends; regulation; antioxidants